TEMPORARY TARSORRHAPHY - USE OF COMMERCIAL GLUE (ELFY): Temporary Tarsorrhaphy - Shoaib, Lt Col Khawaja Khalid; Manzoor, Muhammad; ul haq, Inam; Ishtiaq, Omar (Pakistan Armed Forces Medical Journal, 2010)
Objective: To assess the use of commercial glue (Elfy) for achieving temporary tarsorrhaphyStudy Design: Case seriesPlace and duration of study: Study was conducted at CMH Kharian from January to September 2008.Patients and Method: The various ocular surface disorders which were managed by the temporary tarsorrhaphy with the commercial glue (Elfy) were analyzed. The duration of lid fusion with Elfy and any adverse affects were also noted. Elfy was applied just below the margin of lower eyelid. Then, using a spatula, upper lid was apposed to the lower lid for 1-2 seconds in order to create fusion. If patient required topical treatment, lateral two thirds of the lids were fused and drops instilled through medial one third. In rest of the cases, full length fusion was achieved.Results: In a total of 32 patients Elfy was applied. Eighteen (56%) were males and 14 (44%) were females. Age ranged from six years to seventy five years with mean age of 22.6 years (SD+21.84). Ocular diseases requiring lid fusion included, infective corneal ulcer/abscess in 21 cases (65.6 %), shield ulcer in vernal keratoconjunctivitis in 3 cases (9.4 %), facial palsy in 2 cases (6.2 %), alkali burns in 2 cases (6.2%), neurotrophic ulcer in 2 cases (6.2 %), Mooren ulcer in 1 case (3.1 %), Grave’s disease in 1 case (3.1%). Lid fusion persisted for a mean duration of 7.6 + 4 days (range 2 -20 days). Duration of fusion was less if skin or lashes of upper lid were fused with only skin of lower lid. But it remained for longer duration when eyelashes of both the lids were stuck together. 6 (19%) patients had a burning sensation for fraction of a second, one patient (3%) complained of gritty sensation on skin due to which she removed the Elfy. All the corneal ulcer cases had clinical improvement.Conclusion: Commercial glue (Elfy) is useful as a temporary measure for tarsorrhaphy.